2010
DOI: 10.1183/09031936.00136609
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of digital chest radiography for pulmonary tuberculosis in a UK urban population

Abstract: To the Editors: Population screening for tuberculosis was discontinued in most Western countries, largely due to the decreasing prevalence of the disease. The use of chest radiograph examination for population screening has, therefore, appropriately declined and is now limited to the screening of high-risk groups, such as immigrants 1, prisoners or homeless persons in certain countries 2 and for disease prevalence surveys 3. Chest radiography, however, remains a key tool for the clinical diagnosis of pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 10 publications
0
16
1
2
Order By: Relevance
“…Disagreements were common in the detection of pleural effusions in contrast to the results from Shinsaku et al [5] in Japan and Abubakar et al [24] in London who found a moderate to excellent level of agreement. The predominance of low abundance pleural effusions in our sample (n = 5/6) and their association with other abnormalities could explain these disconcordances.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Disagreements were common in the detection of pleural effusions in contrast to the results from Shinsaku et al [5] in Japan and Abubakar et al [24] in London who found a moderate to excellent level of agreement. The predominance of low abundance pleural effusions in our sample (n = 5/6) and their association with other abnormalities could explain these disconcordances.…”
Section: Discussioncontrasting
confidence: 54%
“…For the detection of ADP, inter-observer agreement was good (K = 0.61) between pneumologists and moderate (K = 0.55) between radiologists. In a similar study conducted in 2010 in London, Abubakar et al [24] reported a poor agreement between both pneumologists and radiologists. The frequent association of ADP with pulmonary tuberculosis and the high prevalence of tuberculosis in our environment could explain this difference.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…By limiting suspects to those with typical infiltrates, the sensitivity dropped to 73% 20. In a study from the UK, Amsterdam and Rotterdam looking at newer digital chest X-ray technology, the sensitivity of radiologists and chest physicians for detecting culture-positive TB on chest X-ray was a similar 77% 21. HIV-coinfected TB patients are less likely to have typical chest X-ray infiltrates, especially with declining CD4 cell counts 22.…”
Section: Traditional Diagnosticsmentioning
confidence: 99%
“…Previous studies suggest that variability in CXR interpretation among raters is attributed to subjective reading accompanied by insufficient experience or different professional background of the raters [7,10-12]. However, the relationship between agreement levels and relevant factors that may cause disagreement, particularly influence of medical background including different national origins has not been characterized.…”
Section: Introductionmentioning
confidence: 99%